Genetic polymorphisms influencing response to lithium - Serretti, Alessandro (Henry Stewart Talks, 2007)
Lithium treatment in the long-term maintenance of mood disorders, The issue of evaluating lithium response, Role of genetic factors, Mechanism of action of lithium candidate genes in lithium response, Inositol polyphosphate 1- phosphatase (INNP1), Gamma-1 isoenzyme of phospholipase C (PLCG1), Tryptophan hydroxylase gene (TPH, A218C), Serotonin transporter gene (5-HTTLPR), Glycogen synthase kinase 3-beta (GSK3B-50 T/C)
Archived at 2021/02/25